Using global datasets to estimate flood exposure at the city scale: an evaluation in Addis Ababa - Carr, A. B.; Trigg, M. A.; Haile, Alemseged Tamiru; Bernhofen, M. V.; Alemu, Abel Negussie; Bekele, Tilaye Worku; Walsh, C. L. (Frontiers Media, 2024)
Introduction: Cities located in lower income countries are global flood risk hotspots. Assessment and management of these risks forms a key part of global climate adaptation efforts. City scale flood risk assessments necessitate flood hazard information, which is challenging to obtain in these localities because of data quality/scarcity issues, and the complex multi-source nature of urban flood dynamics. A growing array of global datasets provide an attractive means of closing these data gaps, but their suitability for this context remains relatively unknown.